Analysis of Students’ Mathematical Communication Skills in Solving Problems Assisted by the Symbolab Application - Hetty Elfina; Izwita Dewi; Faiz Ahyaningsih (MASI Mandiri Edukasi, 2026)
Mathematical communication skills are essential in enabling students to express mathematical ideas through symbols, models, and visual representations. However, many Indonesian students still experience difficulties, particularly when solving story-based problems. This study aimed to analyse students’ mathematical communication skills in solving linear programming story problems using the Symbolab application. The research employed a descriptive qualitative design involving 32 tenth-grade students at Madrasah Aliyah Swasta Plus Al Ulum Medan. Data were collected through five story problems and follow-up interviews with selected students representing each ability level. The result showed that 37,5% of students were in the low category, 37,5% in the medium category, and 25% in the high category of mathematical communication skills. Most students had difficulty translating story problems into mathematical models, which led to errors in graph construction, shading region determination, and final computations. Although the Symbolab application helped students visualise graphs and follow solution steps, students still had to construct mathematical models from the problems independently. These findings suggest that while the Symbolab application can support visualisation and solution steps, explicit instruction and practice in translating word problems into mathematical models remain crucial for developing students’ mathematical communication skills.